(untitled) (Minerva, 2020)
The Legenda pulcra de translacione capitis s. Iacobi is the story of the journey that Pedro Alfonso, abbot of Santa María de Carvoeiro (diocese of Braga), made to Jerusalem in search of the head of Saint James the Great which had been robbed, and its later return to Hispania, where the sacred relic came to Queen Urraca of León’s power. Urraca took the head to the Cathedral of Santiago de Compostela. This paper analyses the contents and sources of the text and suggests dating it between the last third of the 12th century and the first third of 13th century. Finally, it offers the critical edition and translation of the text.